Potency of Alluvial Mineral of Luk Ulo River with XRD and AAS in Kebakalan Village Kebumen - Edy Nursanto; Afroza Pratiwi; Eddy Winarno; Bambang Sugiarto; Riria Zendy Mirahati (Eksergi, 2022)
Based on petrographic data, XRD, and fluid inclusions, it was interpreted that the quartz veins associated with low sulfide in Karangsambung area underwent 2 stages of system change from mesothermal system to epithermal system. This means showing the mineral potential contained in material, including on the Luk Ulo River where alluvial deposits are present. Therefore, what needs to be done next is to determine the composition of the material of the alluvial material in the Luk Ulo River, Kebakalan Village using XRD, and AAS so that its potential is known. This research is limited to mineral potential in XRD and AAS (Au, Ag, and Cu) in 2 samples, A (sand) and B (rock). XRD results on samples A and B showed that quartz (SiO2) had the highest percentage (30-50%) compared to other minerals. While the results of the AAS tests showed that the highest Au and Ag contents were in sample B and Cu in sample A with total of 19.30 g/ton Au, 8.67 g/ton Ag, and 62.88 g/ton Cu. Meanwhile, the lowest total Au and Ag were in sample A and Cu was in sample B which amounted to Au 11.32 g/ton, Ag 8.67 g/ton, and Cu 34.86 g/ton.